Efficacy and Safety of Risankizumab for the Treatment of Hidradenitis Suppurativa: A Phase 2, Randomized, Placebo-Controlled Trial - Alexa B. Kimball; Errol P. Prens; Thierry Passeron; Emanual Maverakis; Irina Turchin; Stefan Beeck; Leonidas Drogaris; Ziqian Geng; Tianyu Zhan; Izabella Messina; Falk G. Bechara (Adis, Springer Healthcare, 2023)
Abstract Introduction Hidradenitis suppurativa (HS) is a chronic, immune-mediated skin condition characterized by inflammatory lesions that can cause pain, impaired physical activity, and reduced quality of life. This study evaluated the efficacy and safety of risankizumab, a humanized immunoglobulin G1 monoclonal antibody that specifically inhibits interleukin 23 by binding to its p19 subunit, for the treatment of HS. Methods This phase II multicenter, randomized, placebo-controlled, double-blind study investigated the efficacy and safety of risankizumab in patients with moderate-to-severe HS. Patients were randomized 1:1:1 to receive subcutaneous risankizumab 180 mg; risankizumab 360 mg; or placebo at weeks 0, 1, 2, 4, and 12. Patients initially randomized to placebo received blinded risankizumab 360 mg at weeks 16, 17, and 18; patients initially randomized to risankizumab received blinded matching placebo at the same time points. From weeks 20-60, all patients received open-label risankizumab 360 mg every 8 weeks. The primary endpoint was the achievement of HS Clinical Response (HiSCR) at week 16. Safety was assessed by monitoring of treatment-emergent adverse events (TEAEs). Results A total of 243 patients were randomized (risankizumab 180 mg, n = 80; risankizumab 360 mg, n = 81; placebo, n = 82). HiSCR was achieved by 46.8% of patients with risankizumab 180 mg, 43.4% with risankizumab 360 mg, and 41.5% with placebo at week 16. The primary endpoint was not met, and the study was terminated early. Incidence of TEAEs, severe TEAEs, TEAEs considered possibly related to study drug, and TEAEs leading to discontinuation of study drug were generally low and comparable across treatment groups. Conclusion Risankizumab does not appear to be an efficacious treatment for moderate-to-severe HS. Future studies to understand the complex molecular mechanisms underlying HS pathogenesis and develop improved therapies are warranted. Trial Registration ClinicalTrials.gov identifier: NCT03926169.